2015
DOI: 10.1371/journal.pone.0142782
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Analysis Reveals the Negative Effects of Attention-Deficit/Hyperactivity Disorder (ADHD) Symptoms on Friend-Based Student Networks

Abstract: IntroductionSocial network analysis has emerged as a promising tool in modern social psychology. This method can be used to examine friend-based social relationships in terms of network theory, with nodes representing individual students and ties representing relationships between students (e.g., friendships and kinships). Using social network analysis, we investigated whether greater severity of ADHD symptoms is correlated with weaker peer relationships among elementary school students.MethodsA total of 562 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Moreover, our findings agree with previous investigations which also observed that social relationships were improved by cooperative play in children [53,54] and that participation in a mindfulness-based prosocial training curriculum was able to promote self-regulation and prosocial behavior in young children [3,6]. While recent studies have evaluated the peer relationships of children using social network analysis (e.g., [63][64][65][66]), to the best of our knowledge, few studies have been carried out to evaluate changes in social dynamics after applying an intervention. Interestingly, the activities carried out in the present investigation seem to have helped decrease self-centeredness in children, enabling them to connect with others and develop empathic concern, thus promoting higher richness of social diversity.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our findings agree with previous investigations which also observed that social relationships were improved by cooperative play in children [53,54] and that participation in a mindfulness-based prosocial training curriculum was able to promote self-regulation and prosocial behavior in young children [3,6]. While recent studies have evaluated the peer relationships of children using social network analysis (e.g., [63][64][65][66]), to the best of our knowledge, few studies have been carried out to evaluate changes in social dynamics after applying an intervention. Interestingly, the activities carried out in the present investigation seem to have helped decrease self-centeredness in children, enabling them to connect with others and develop empathic concern, thus promoting higher richness of social diversity.…”
Section: Discussionsupporting
confidence: 91%
“…Congruent with research indicating that adolescents with ADHD struggle with social relationships, the ADHD group endorsed family problems, poor assertiveness, feelings of alienation, social avoidance, and interpersonal distrust in contrast to the MMPI‐A‐RF norms. Consistent with our prediction that the two clinical groups would differ in interpersonal difficulties according to diagnostic characteristics, the non‐ADHD clinical group reported more internalizing complaints such as social avoidance, while the ADHD group acknowledged associating with negative peers and mistrust in relationships (as measured by the RC3 scale), findings consistent with the observations of Kim et al (2015), who noted that in contrast to peers, Korean children with ADHD experienced social isolation and fewer supportive relationships. Interestingly, despite significant zero‐order correlations between RC3 and ADHD diagnosis, RRR values were nonsignificant at each cutoff level, likely reflecting the reduced statistical power associated with dichotomizing RC3 scores.…”
Section: Discussionsupporting
confidence: 91%
“…Interpersonal relationships are emphasized in Asian countries, as building appropriate peer relationships is considered a crucial protective factor against victimization, depression, suicidality, and academic problems (Chou et al, 2016; Liu et al, 2017). Kim et al (2015) observed that Korean adolescents who met the criteria for ADHD reported lower quality of social interactions, fewer friends, and feelings of alienation when compared with their peers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DC methods lead to greater information resonance in the brain, making network connectivity more convenient. Moreover, increases in DC indicate lower metabolism, and can increase the speed of obtaining brain region connectivity (Kim et al, 2015; Park and Park, 2016). The brain regions commonly used as central areas include the posterior cingulate cortex, lateral temporal lobe, lateral parietal lobe, medial and lateral prefrontal cortex (Buckner et al, 2009a,b).…”
Section: Introductionmentioning
confidence: 99%